Alice Salomon (Germany), President 1928/29-1946 - Carola Kuhlmann (Social Work & Society, 2008)
Salomon belongs to the known and nevertheless unknown 'pioneers' of social work in the world. She founded one of the first Schools of Social Work (Berlin 1908) and was the first president of the International Association of Schools of Social Work (1929-1937 [2] ). Her theoretical work however is almost forgotten or not really part of the debate about social work history. This is partly due to her expulsion from Germany in 1937, partly it is the 'normal' destiny of female intellectuals (Staub-Bernasconi 1991). The lacking or superficial interest in her theoretical work led to many - still existing - prejudices about her definition of social work as a female, a 'motherly' profession. Studying her more than 350 articles and more than 30 (text-)books (see Kuhlmann 2000) reveals a great treasure of knowledge about the character and the methods of social work, about social and economic background factors of poverty and about the ethics of the social profession. Above all, Salomon's theoretical work represents one of the earliest and till today almost unique feministic approaches to social work theory.